TiO2 – ZnO nano composite films in solar driven water splitting performance / Nur Azimah Abd Samad - Nur Azimah , Abd Samad (2016)
Solar driven water splitting system is a key target for the development of sustainable hydrogen economy for future energy system. The formation of self-organized zinc oxide (ZnO) nanostructures is essential for high efficiency in photoelectrochemical (PEC) solar driven water splitting system. Comprehensive investigations on different parameters, such as heat treatment, stirring process, reaction temperature, exposure time, and applied potential were conducted in order to control the specific architecture of ZnO nanostructures. Based on the results obtained, ZnO nanorod; diameter in a range of 35.0 – 65.0 nm and length in a range of 210.0 – 280.0 nm were successfully formed via electrodeposition technique in an electrolyte containing 0.05 mM ZnCl2 and 0.1 M KCl at 1.0 V for 60 min. Continuous efforts have been exerted to further improve the PEC water splitting performance by incorporating an optimum content of TiO2 nanoparticles on ZnO nanorod film via dip-coating technique. The modification of ZnO nanorod was to overcome several drawbacks, including poor visible light absorption and high recombination losses of charge carrier. It was found that 0.25 at% of TiO2 nanoparticles coated on ZnO nanorod film and subsequently heat treated at 400 °C demonstrated a maximum photocurrent density of 19.78 mA/cm2 (1.66 % photoconversion efficiency) under UV ray (300 nm) and 14.75 mA/cm2 (2.18 % photoconversion efficiency) under visible light (500 nm). This performance was approximately 2-3 times higher than the ZnO nanorod film. The presence of Ti element in hybrid TiO2-ZnO film (below 1 at% Ti) showed an improvement of photocurrent density and photoconversion efficiency because it acted as an effective mediator to trap the photo-induced electrons and minimize the recombination of charge carriers. It is a well-known fact that phenomenon of charge carriers-separation effect at type-II band alignment of Zn and Ti might further enhanced the transportation for photo-induced charge carriers during illumination. Contra in results appeared with the redundant of TiO2 nanoparticles coated on ZnO nanorod wall surface. PEC water splitting performance became poor because TiO2 nanoparticles formed independent layers and electrons in TiO2 were trapped by the excess amount of oxygen and could not be transferred to ZnO.